Carl Friedrich von Weizsäcker: Pioneer of Physics, Philosophy, Religion, Politics and Peace Research
XXVIII, 166 p. 68 illus., 46 illus. in color.
Keywords: This book offers a collection of texts by Carl Friedrich von Weizsaecker (1912-2007), a major German universal scientist who was a pioneer in physics, philosophy, religion, politics and peace research. He started as an assistant to the physicist, Werner Heisenberg, held professorships in theoretical physics (Strasbourg), physics (Goettingen) and philosophy (Hamburg) and was a co-director (with Juergen Habermas) of a Max Planck Institute for Research into living conditions in a world of science and technology in Starnberg. This unique anthology spans the wide scope of his innovative thinking including his philosophical self-reflections, on peace, nuclear strategy, security and defensive defense, on nuclear energy, on the conditions of freedom, on his experience of religion, including poetry from his early youth. Most texts appear in English for the first time and are selected for use in seminars on physics, philosophy, religion, politics and peace research.